Experimental paracoccidioidomycosis in hamsters (Mesocricetus auratus): Gestational interactions - de Carvalho, MGF; Montenegro, M. R. (Kluwer Academic Publ, 1999)
Paracoccidioides brasiliensis is a dimorphic fungus presenting specific steroid hormone receptors, both in the yeast and mycelial forms and estrogen inhibits the transition from mycelium to yeast. In the acute phase, the disease occurs with equal frequency in both sexes but in adults, females are spared. Placental fungal infection has been reported, but references to fetal infection have not been confirmed. We used 78 Syrian female hamsters divided into 3 groups: GI consisted of 30 infected mated females, GII of 20 infected unmated females and GIII of 28 uninfected mated females. Animals of group I were mated 4 weeks after infection and half of them were submitted to cesarean section on day 15 after successful mating; the other half was maintained and submitted to cesarean section and sacrificed 14 weeks after infection. Half of the animals of group II were sacrificed seven weeks and the other half 14 weeks after infection. Uninfected animals of group III were treated the same as the animals of group I. The animals were infected with strain 18 of P. brasiliensis by the intracardiac route. We evaluated the disease by the volume of granulomas in different organs, number of fungi in liver and spleen and the immunologic responses [ELISA, Double Immunodifusion (DID), Delayed Hypersensitivity Skin Test (DHT) and Macrophage Migration Inhibition (MMI)]. We studied the infection through the gestation by evaluation of the abortions, morphologic and clinic examinations of the fetuses. Our results showed that the infection did not transfer to the fetus through the placenta, but the number of abortions was larger among infected females. The newborns of GI females were smaller, weighed less and showed little vitality. The disease was more severe and disseminated in infected mated females, especially in the second sacrifice 14 weeks after inoculation, when the total volume of granulomas in them (56.3 mm) was much greater than in the infected unmated females (12 mm).
Keywords: experimental paracoccidiodomycosis; gestational interactions